The team effect on doping in professional male road cycling (2005-2016) - Aubel, O.; Lefèvre, B.; Le Goff, J. M.; Taverna, N. (Scandinavian Journal of Medicine & Science in Sports, 2019)
This article questions organizations` (clubs, teams, etc) responsibility in doping use from the case of anti-doping rules violations (ADRVs) sanctioned by the Union Cycliste Internationale in professional cycling. We built a database with 271 caught riders among 10 551 professional riders employed from 2005 to 2016 in the three first world divisions. We developed a time-discrete event history model with a multilevel perspective to consider if the ADRV is related to the characteristic of a rider's career path (level 1) and/or the team by which the rider is employed (level 2). Our results confirm two hypotheses: Beginning a career before 2005 or after the age of 22 increased the risk of being caught. Each additional year in the pack increased the risk, despite the fact that a sanctioned rider's career duration average is 7.8 years (3.9 for the others). These caught riders have experienced a more tumultuous career with team changes and an interrupted path. A 2.45 Median Odds Ratio led us to assert a team effect on ADRV. By a team residual effect calculation, we identify 17 teams with a significant effect within the 129 that experienced an ADRV. Our results allow us to emphasize that to understand doping we must take into account work and employment condition, as well as team's organization. This approach completes the dominant "methodological individualism" perspective that considers athletes as analytical units and provides guidelines to the anti-doping bodies that focus their action on individuals.